Peningkatan Literasi Masyarakat Melalui Pojok Baca Sekaput di Warung Kopi - Suryadin, Asyraf; Maulana, Said Akhmad; Amalia, Runi Alcitra (Universitas Muhammadiyah Yogyakarta, 2021)
The establishment and socialization of Sekaput Reading Corner to increase public interest in reading at coffee shops in Pangkalpinang City is a joint effort to increase literacy and reading interest among coffee lovers since coffee shops do not usually provide a reading corner. This program aimed to improve people’s literacy skills with the support of the Sekaput Reading Corner. At the same time, this program brought reading materials closer to the community while being at the coffee shop. The case observation method was used during the implementation of this program. Accordingly, the program involved 15 coffee shops by providing a reading corner stimulus to 5 selected coffee shops. The results showed approximately 80% of coffee shop customers gave a good response to the Sekaput Reading Corner in the coffee shops. Reflecting on the results, in the future, Sekaput Reading Corner can be applied in every coffee shop by moving from place to place.